Optimal Strategies for Manufacturers with the Reference Effect under Carbon Emissions-Sensitive Random Demand - Baojun Zhang; Shaojian Qu; Panpan Li; Ripeng Huang (Discrete Dynamics in Nature and Society)
In this paper, we study the optimal strategies for a newsvendor system with joint reference effect, carbon emissions-sensitive random demand, and strategic customers’ behavior. The newsvendor’s decisions are to determine the selling price, production quantity, and carbon emissions under exogenous and endogenous price cases, respectively. We also explore how the loss aversions affect the newsvendor’s decisions. It is shown that the newsvendor has a uniquely optimal policy. The influence of the reference effect makes the final decisions deviate from the optimal solutions of the classical model. Furthermore, the sensitivity analysis indicates that the loss aversions have a great impact on the newsvendor’s decisions. Finally, more managerial implications are derived by numerical simulations.